Hospital-Based Donor Recruitment and Predonation Serologic Testing for COVID-19 Convalescent Plasma. Issue 4 (5th January 2021) - Balcerek, Joanna; Trejo, Evelin; Levine, Kendall; Couey, Paul; Kornberg, Zoe V; Rogine, Camille; Young, Charlotte; Li, P Jonathan; Shy, Brian R; Taylor, Jordan E; Bakhtary, Sara; Friedlander, Terence; et al.
Abstract: Objectives: Serologic testing for antibodies to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in potential donors of coronavirus disease 2019 (COVID-19) convalescent plasma (CCP) may not be performed until after blood donation. A hospital-based recruitment program for CCP may be an efficient way to identify potential donors prospectively Methods: Patients who recovered from known or suspected COVID-19 were identified and recruited through medical record searches and public appeals in March and April 2020. Participants were screened with a modified donor history questionnaire and, if eligible, were asked for consent and tested for SARS-CoV-2 antibodies (IgG and IgM). Participants positive for SARS-CoV-2 IgG were referred for CCP collection. Results: Of 179 patients screened, 128 completed serologic testing and 89 were referred for CCP donation. IgG antibodies to SARS-CoV-2 were detected in 23 of 51 participants with suspected COVID-19 and 66 of 77 participants with self-reported COVID-19 confirmed by polymerase chain reaction (PCR). The anti–SARS-CoV-2 IgG level met the US Food and Drug Administration criteria for "high-titer" CCP in 39% of participants confirmed by PCR, as measured by the Ortho VITROS IgG assay. A wide range of SARS-CoV-2 IgG levels were observed. Conclusions: A hospital-based CCP donor recruitment program can prospectively identify potential CCP donors. Variability in SARS-CoV-2 IgG levels has implications for the selection of CCP units for transfusion.